Relationship between Management Commitment; OSH Behavior; Work Shift with Occupational Accident at RSUD Kanjuruhan Kepanjen Malang Regency - Hesti Diana Rosia Puspitasari; Yayi Suryo Prabandari; Santosa Budiharjo (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
As a community service, hospitals are a means to deal with health, recovery and health care issues. Potential hazards in the hospital may be caused by biological factors, chemical factors, ergonomics factors, physical factors and psychosocial factors. The dangers of the above factors can lead to workplace accidents or PAK which can cause a decrease in physical or mental ability, disability, or even death. To determine the relationship between management commitment and the incidence of work accidents at the Risk Unit in RSUD Kanjuruhan Malang Regency. Quantitative research, with cross sectional study and needed 55 hospital worker from 6 risk units. The result of Pearson correlation analysis of management commitment, OSH behavior and work shift have the significant correlation with work accident. Both of management commitment and OSH behavior have the negative correlation which mean that higher management and behavior can decrease the accidents. The result of multivariate test was obtained by F value of 9.93 with p=0,000 which means that management commitment, OSH behavior and work shift simultaneously have significant effect to work accident. There is a significant correlation between management commitment, OSH behavior and work shift with occupational accident.